CULTURAL REPRESENTATION IN THE PRACTICE OF ANDRAGOGY IN THE ACADEMIC - Janawi; Jamali, Yusra; Pratama, Dinar; Musa; Anwar, Saiful; Subardi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2022)
This study explores the implementation of andragogical principles in higher education, with a focus on the context of STAIN SAS Bangka Belitung. Andragogy, as a learner-centered approach, emphasizes the unique needs of adult learners, including self-directed learning, the integration of prior experiences, and the relevance of education to real-world applications. Through a mixed-methods approach, this research evaluates the effectiveness of a professional development program designed to enhance lecturers' understanding and application of andragogical principles. Data were collected through pre- and post-training assessments, student evaluations, and interviews with lecturers. The findings reveal a significant improvement in lecturers' knowledge of andragogy, with post-test scores increasing by 23.9% compared to pre-test results. Student evaluations further indicated that lecturers effectively applied andragogical principles, particularly in understanding learners' self-concept and fostering a learner-centered environment. However, challenges were identified in integrating students' prior experiences and aligning course content with andragogical principles. Barriers such as insufficient lecturer innovation, inadequate learning facilities, and students' pragmatic orientations were also noted. Conversely, enablers such as institutional support, training opportunities, and student motivation facilitated the successful adoption of andragogical practices. The study underscores the importance of continuous professional development and institutional support in promoting andragogical approaches in higher education. Recommendations include revising curricula to better reflect andragogical principles, investing in modern learning facilities, and fostering a culture of innovation among lecturers. Future research should explore the long-term impact of andragogical training on teaching practices and student outcomes, as well as the role of institutional policies in sustaining these practices. By addressing these challenges and leveraging existing enablers, institutions like STAIN SAS Bangka Belitung can create more effective and engaging learning environments for adult learners, ultimately enhancing the quality of higher education.